Christianity and conversion among migrants: moving faith and faith movement in a transit area - Carlson, Darren (Theology and mission in world Christianity, 2021)
"In Christianity and Conversion among Migrants, Darren Carlson explores the faith, beliefs, and practices of migrants and refugees as well as the Christian organizations serving them between 2014-2018 in Athens, Greece. This is the first major study of migrant faith communities and refugee centers conducted in Athens. The study traces the travel stories of participants as they leave their home countries and migrate to Athens. Darren Carlson discusses the ways evangelical and Pentecostal Christians served migrants along their journey, how churches and specific refugee centers served and proclaimed the gospel, and the impact Christian witness had on migrants, particularly Muslims, who were converting to evangelical Christian faith"--